2003
DOI: 10.1016/s0022-5223(03)00735-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of elevated creatine kinase MB after coronary bypass surgery and after an acute coronary syndrome: results from the GUARDIAN trial

Abstract: Modest elevations of creatine kinase-myocardial band release (> or =1 and <10 ULN) after coronary artery bypass surgery are not associated with adverse 6-month survival, in contrast to that seen in acute coronary syndrome patients. Routine creatine kinase-myocardial band sampling should be considered in all higher-risk patients undergoing coronary artery bypass surgery procedures to identify the sizable cohort of patients with creatine kinase-myocardial band release > or =10 ULN; these patients may benefit fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
(28 reference statements)
2
10
0
1
Order By: Relevance
“…The Guard During Ischemia Against Necrosis (GUARDIAN) study found a strong relationship between CK elevation Ͼ10 times the ULN and 6-month mortality. 48 Although lower degrees of CK elevation were not associated with mortality in that study, with a longer follow-up, a relationship may have emerged. Other studies have found a graded increase in mortality across the full spectrum of CK elevation, including CK-MB Ͼ3 times the ULN.…”
Section: Periprocedural Myonecrosis In the Setting Of Bypass Surgerymentioning
confidence: 66%
“…The Guard During Ischemia Against Necrosis (GUARDIAN) study found a strong relationship between CK elevation Ͼ10 times the ULN and 6-month mortality. 48 Although lower degrees of CK elevation were not associated with mortality in that study, with a longer follow-up, a relationship may have emerged. Other studies have found a graded increase in mortality across the full spectrum of CK elevation, including CK-MB Ͼ3 times the ULN.…”
Section: Periprocedural Myonecrosis In the Setting Of Bypass Surgerymentioning
confidence: 66%
“…The Guard During Ischemia Against Necrosis (GUARDIAN) study in 2332 CABG patients demonstrated the strongest mortality risk associated with large CK elevations (those above 10ϫ ULN) at 6-month follow-up. 82 Another registry of 3667 CABG patients with 5-year follow-up showed a graded reduction in survival associated with post-CABG CK-MB (CK-MB ϽULN: 80%; CK-MB 1 to 3ϫ ULN: 78%; CK-MB Ͼ3ϫ ULN: 73%; Pϭ0.0008). Every unit increment of CK-MB was independently associated with mortality (odds ratio; 95% CI, 1.04 [1.009 to 1.062]; Pϭ0.0007).…”
Section: Periprocedural MI After Cabgmentioning
confidence: 99%
“…Additionally, at any time during the trial, the primary investigator was able to identify the occurrence of an MI for adjudication by the clinical events committee. Creatine kinase-MB measurements were collected at 4,8,12,16,24,72, and 96 hours postoperatively and were analyzed at a central core laboratory. Electrocardiograms were recorded at patient enrollment as well as at 48 and 96 hours and 14, 30, 90, and 180 days postoperatively.…”
Section: Study End Pointsmentioning
confidence: 99%